Nitrogen Regulator GlnR Controls Redox Sensing and Lipids Anabolism by Directly Activating the whiB3 in Mycobacterium smegmatis - You, Di; Xu, Ying; Yin, Bin-Cheng; Ye, Bang-Ce (Frontiers in Microbiology, 2019)
WhiB3 is a conserved cytoplasmic redox sensor which is required in the infection and lipids anabolism of Mycobacterium tuberculosis. The response of WhiB3 to environmental nutrient and its regulatory cascades are crucial during the persistent infection, while little is known about the relationship between WhiB3 and emergence of nutrient stress in this process. Here, we found that nitrogen regulator GlnR can directly interact with the promoter region of whiB3 and activate its transcription in response to nitrogen availability. The typical GlnR-binding box was identified in the promoter region. Moreover, GlnR controls the cell resistance to redox stress and SL-1 lipids anabolism by directly activating the expression of whiB3. These results uniquely demonstrate that GlnR regulated redox sensor WhiB3 at transcriptional level and mediated the interplay among nitrogen metabolism, redox sensing, and lipids anabolism.